Stabilisasi Tanah Ekspansif Dengan Campuran Abu Batu Bara Dan Abu Terbang Batu Karang Dengan Aplikasi Timbunan Tipe Urugan Tanah - Sompie, Fergy A. E.; Manoppo, Fabian J.; Sompie, Oktovian B. A. (Sam Ratulangi University, 2018)
The expansive soil is a soil which clay content has a potential for shrinkage due to changes in water content,causing changes in the volume of soil. The expansive soil is a problematic type of soil in a construction project,especially for the construction of a base ground of a building because it contains montmorillonite minerals withthe largest surface area and is very easy to absorb water. The ground with high shrinkage value, the waterbecomes very influential to the behavior physical and mechanical soils. Therefore, in conducting theconstruction planning, investigation or soil investigation must be conducted in order to know the physical andmechanical properties of the soil if the soil contains clay mineral that is expansive so that we are able to stabilizeto increase the strength and carrying capacity of the soil. Stabilization is done by using fly ash (fly ash) coal androcks. The objective of this research is to obtain the shear parameter value after mixing coal fly ash and coral aswell as to know the application on landfill type by using 2D plaxis program to know the value of decrease,excess pore water pressure and safety factor. The composition of the mixture used for obtaining shear parametervalues is coal fly ash + ash, soil + rock fly ash and soil + coal fly ash and coral reefs of 2%, 4%, 6%, 8%respectively. For applications on the design of embankment type of soil type taken mixture composition is soil +coal fly ash, soil + fly ash rock and soil + fly ash coal and coral reef 2% and 8% respectively. The sample of thesoil is taken in Warembungan Village, Pineleng District. Investigation of physical and mechanical properties ofthe soil is also carried out such as filter and hydrometer analysis, moisture content, specific gravity, atterbergtest, consolidation test to determine the development (swelling) and CBR Laboratory. The results showed that the addition of fly ash coal, rock and coal + corals showed the variation of cohesionvalues and shear angle in the increasing percentage of fly ash coal, coal and coral + coal. The original soilcohesion value is 1.72 t / m2 and the inner shear angle is 11.8 °. In mixing between expansive soil + fly ash coalmaximum cohesion value was found at 8% addition which was 1.90 t / m2 while the shear angle value rose to17,93 ° at 6% addition. In mixing of expansive soil + fly ash of rock the maximum cohesion value is in 2%addition which is 1.48 t / m2 while the shear angle value rises to 30,10 °. In mixing of expansive soil + fly ashcoal + coral maximum cohesion value is in 2% addition which is 0,58 t / m2 whereas shear angle value rose to38,80 °. For embankment applications with 0% or no mixture of decreasing values, excess pore water and safetyfactors are 0.312 m, 2.34 kN / m2, and 1.18, respectively. In mixing between expansive soil + fly ash coaldecreased slightly on 8% variation where the value of decrease, excess pore water and safety factor were 0.35 mrespectively; 0.565 kN / m2, and 1.117. In mixing between expansive soil + fly ash rocks, the decreasing value,excess pore water and safety factor increased in 2% variation respectively to 0.188 m; 0.777 kN / m2, and 1,253.In mixing of expansive soil + fly ash coal + coral, decreasing value, excess pore water and safety factorincreased in 2% variation to 0.267 m respectively; 0.657 kN / m2, and 1.245.The addition of fly ash to coralreefs is more effective and efficient than coal in raising the value of soil shear strength parameter but in landfillapplication will be more effective if it is done the addition of both fly ash coal + coral to get smaller decreasevalue and safety factor greater than. It is recommended to first base soil stabilization and use better materialselection for embankment to further increase the safety factor and minimize the decrease value. Keywords: expansive soil, high shrinkage, stabilization, fly ash coal, coral reef ash, safety facto